An Integrated Framework for Jobs in Fragile and Conflict Situations - World Bank Group (World Bank, Washington, DC, 2016)
Jobs are a high priority for development and stability in fragile and conflict-affected situations. Jobs contribute to poverty reduction, productivity and economic growth, and can promote social cohesion and reduce the risk of violence. However, the jobs environment is particularly challenging in situations affected by fragility, conflict, and violence (FCV), with various combinations of high political, economic and social risks, weak institutional capacity, a difficult political economy, and significant constraints on financial resources to support recovery and reconstruction. Thus, fragile situations have an urgent need for well-structured assistance to address these challenges and create job opportunities. To help strengthen its engagement on jobs in FCV, the World Bank Group (WBG) has developed an integrated jobs framework. The purpose of this note is to describe the framework, which has been adapted from the WBG’s general jobs framework to incorporate the above dimensions of fragility and instability, and to outline the policy and operational implications for both the short and long run. Ultimately, the aim is to improve the support the WBG can offer to expand job opportunities across the range of FCV contexts.